2018
DOI: 10.1249/mss.0000000000001539
|View full text |Cite
|
Sign up to set email alerts
|

No Effect of Muscle Stretching within a Full, Dynamic Warm-up on Athletic Performance

Abstract: Participants felt they were more likely to perform well when stretching was performed as part of the warm-up, irrespective of stretch type. However, no effect of muscle stretching was observed on flexibility and physical function compared with no stretching. On the basis of the current evidence, the inclusion of short durations of either static or dynamic stretching is unlikely to affect sprint running, jumping, or change of direction performance when performed as part of a comprehensive physical preparation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 26 publications
3
56
0
5
Order By: Relevance
“…Recent studies incorporating all aspects of a full warm-up (i.e. aerobic activity, SS, DS, and dynamic sport specific activity) have not shown any performance deficits with a moderate duration of SS either [55,56]. Although 60 s of SS per muscle group did not result in performance decreases with a full warm-up, more excessive SS of 2 min per muscle group could still induce some deficits [56].…”
Section: Stretching Within a Full Warm-upmentioning
confidence: 94%
See 2 more Smart Citations
“…Recent studies incorporating all aspects of a full warm-up (i.e. aerobic activity, SS, DS, and dynamic sport specific activity) have not shown any performance deficits with a moderate duration of SS either [55,56]. Although 60 s of SS per muscle group did not result in performance decreases with a full warm-up, more excessive SS of 2 min per muscle group could still induce some deficits [56].…”
Section: Stretching Within a Full Warm-upmentioning
confidence: 94%
“…Although 60 s of SS per muscle group did not result in performance decreases with a full warm-up, more excessive SS of 2 min per muscle group could still induce some deficits [56]. Furthermore, while the inclusion of SS within a full warm-up did not enhance physical performance (nor impair it), there was a positive psychological effect as the individuals felt more confident of achieving high performance in the ensuing sports-related tests [55]. The meta-analysis from Behm et al [1] also highlighted a number of common limitations of the typical stretching and subsequent performance studies published in the literature.…”
Section: Stretching Within a Full Warm-upmentioning
confidence: 94%
See 1 more Smart Citation
“…Warming-up also seeks to improve performance and reduce lesions in physical exercises [6,7]. In those of short duration and high intensity, it potentiates the rapid production of energy, producing more intense contractions; and in those of long duration, previously activates the energy production of the aerobic component; reduces the slow aerobic component and toxic metabolites, such as lactic acid.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of stretching on preventing lesions and performance are contradictory in the literature, mainly due to the possible variations among techniques and sports involved [7,16,17]. In a systematic review, Hebert, et al [18] concluded that stretching before, after; or before and after physical training did not produce ly 90°, palms of the hands facing outwards.…”
Section: Methodsmentioning
confidence: 99%